An integrated, multistudy analysis of the safety of Ann Arbor strain live attenuated influenza vaccine in children aged 2–17 years - Ambrose, Christopher S. (Blackwell Publishing Ltd, 2011)
Please cite this paper as: Ambrose et al. (2011) An integrated, multistudy analysis of the safety of Ann Arbor strain live attenuated influenza vaccine in children aged 2–17 years. Influenza and Other Respiratory Viruses 5(6), 389–397. Background  Trivalent, Ann Arbor strain, live attenuated influenza vaccine (LAIV) is approved in several countries for use in eligible children aged ≥2 years. Objective  To describe the safety of Ann Arbor strain LAIV in children aged 2–17 years. Methods  An integrated analysis of randomized, controlled trials of LAIV. Results  A total of 4245 and 10 693 children received ≥1 dose of LAIV in year 1 of 6 trivalent inactivated influenza vaccine (TIV)‐controlled and 14 placebo‐controlled studies, respectively; 3212 children were revaccinated in year 2 of 4 placebo‐controlled studies. Compared with placebo for days 0–10 post‐vaccination, LAIV recipients exhibited increased runny/stuffy nose (+7%), headache (+7%), and tiredness/decreased activity (+2%) after dose 1; and a higher rate of decreased appetite (+4%) after year 2 revaccination. Compared with TIV, only runny/stuffy nose was increased (dose 1, +12%; dose 2, +4%). Compared with initial vaccination, LAIV reactogenicity was lower after dose 2 in year 1 and revaccination in year 2. Unsolicited adverse events (AEs) increased with LAIV in some comparisons were headache, nasal congestion/rhinorrhea, rhinitis, and pyrexia; ear pain and lower respiratory illness were decreased. There was no evidence of an increase in any potential vaccine‐related serious AE in LAIV recipients. Among children aged 2–17 years and specifically aged 24–35 months, there was no evidence that lower respiratory illness or wheezing illness occurred at a higher rate in LAIV recipients. Conclusion  This analysis supports the safety of Ann Arbor strain LAIV in children aged 2–17 years and provides a consensus assessment of events expected after vaccination.